ENTREPRENEURSHIP ON STRATEGIES TO BUILD COMPETITIVE ADVANTAGES OF RIAU SPECIALTY FOOD PRODUCTS - Fatkhurahman Fatkhurahman; Sidik Priadana; Ellen Rusliati (Faculty of Economics and Business, University of Pasundan, 2019)
The competitive advantage of small and medium industries (SMIs) is a concern in the preparation to face the conditions of developing and growing into large industries. This research, conducted in Riau Province with regard to competitive advantage of SMIs, can provide an overview of the real conditions in the Indonesian border region. Survey was conducted to 247 respondents of small and medium food industry managers using questionnaires. The collected data were analyzed using SEM WarpPLS analysis. The results showed that the competitive advantage of small and medium food industries in Riau Province proved to be influenced by the application of superior strategies, thus, the use of superior strategies was needed to achieve competitive advantage. An effective strategy for business managers is to build entrepreneurship of the business managers through building the ability to see market opportunities and also courage in facing competitors with various risks.